熟練看護師が回復期の脊髄損傷患者の変化する思いに対して支援するプロセス - 飯田 倫佳; 加藤 真由美; 田中 浩二; 谷口 好美 (日本看護科学会誌, 2023)
要旨　目的：熟練看護師が回復期の脊髄損傷患者の変化する思いへ，支援するプロセスを明らかにすること．　方法：「脊損患者の変化した思いに対して支援を行った経験」について熟練看護師14名に半構成的面接法を実施し，M-GTAを用いて分析した．　結果：熟練看護師は，リハ病棟転入後の不安や恐怖に対して【安心して療養生活を送られる支援】をし，〈埋蔵資源の意識化と増幅の支援〉［他者に向ける怒りと自分の内に向ける落胆の緩和］や多職種と連携し［新たな排泄テクニック獲得意欲の支援］を組み合わせて実践する中で，〈揺れ動く意欲の安定化〉を図りながら【その人らしさの再認識支援】を行い，家族に迷惑をかけるために自分が存在して良いのかと揺らぐ思いに対して【存在意味の否定的認知からの解放支援】をしていた．　結論：変化する思いを支えるには，支援を組み合わせて，微調整しながら多職種と連携し，患者との対話を含め支援し続けていく必要がある． 　Purpose: To clarify the process through which skilled nurses continue providing support for the changed feelings in patients with spinal cord injuries in the recovery period.　Methods: Semi-structured interviews were conducted with 14 skilled nurses to investigate their "experience with providing support for the changed feelings of patients with spinal cord injuries." Thereafter, these interviews were analyzed using M-GTA.　Results: To address the anxiety and fear of patients transferred to the rehabilitation ward, skilled nurses collaborated with multiple professionals to provide "support for receiving secure medical care," "support for increasing awareness and amplification of buried self-resources," "support for alleviating expressed anger and internal discouragement," "support for motivation to acquire new excretion techniques" and "support for stabilization of fluctuating will." These services are intended to "help patients reconceptualize their individuality." In addition, for patients who questioned their existence because of becoming a nuisance to their families, the nurses provided "support to free them from negative perceptions regarding the meaning of their existence."　Conclusion: To support the changing feelings of patients, it is necessary for nurses to combine and fine-tune their support from time to time, and to continue providing support in cooperation with multiple professionals.